Mental health of urban population: a call to action - Caleffi, Felipe; Marasini, Gisele (Journal Of Exact Sciences and Technological Applications, 2025)
Rapid urbanization across the globe significantly challenges the mental health of urban populations. This paper explores the intricate relationship between urban living and mental well-being, highlighting the urgent need for comprehensive research and precise interventions to counteract the negative impacts of urban life on mental health. It emphasizes the critical role of adopting a multidisciplinary and intersectoral approach, weaving together public policy, urban planning, community initiatives, and readily accessible mental health services. By focusing on the determinants of mental health in urban settings, such as environmental, social, and economic factors, the study advocates for strategies that improve access to green spaces, bolster social cohesion, and promote economic fairness. It also underscores the transformative potential of technology in making mental health services more accessible and the pivotal importance of interdisciplinary collaboration in navigating the intricacies of urban mental well-being challenges. This paper issues a call to action, urging policymakers, urban planners, and health professionals to place mental health at the forefront of urban agendas, thereby cultivating environments conducive to psychological well-being and effectively tackling the distinctive challenges of urban living.